2019
DOI: 10.1186/s13705-019-0231-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of photovoltaic and battery systems from the prosumer-oriented total cost of ownership perspective

Abstract: Background: In the context of the German energy transition, the number of domestic households covering part of their electricity consumption from their own photovoltaic system is constantly increasing. Some even use battery storage systems to store excess power for later use, which increases the degree of self-sufficiency and, according to the providers of such systems, should yield financial advantages for the so-called prosumer. Methods: We used the Prosumer-Oriented Total Cost of Ownership method to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Is it however also demonstrated that the battery power cannot be too great compared to the battery energy constraint, otherwise the battery will be drained too quickly, and the peak demand for a period of high demand will not be reduced by combining grid and batty power. This can also be seen in [16], [17]. There are some minor variations from this trend.…”
Section: Discussionmentioning
confidence: 54%
“…Is it however also demonstrated that the battery power cannot be too great compared to the battery energy constraint, otherwise the battery will be drained too quickly, and the peak demand for a period of high demand will not be reduced by combining grid and batty power. This can also be seen in [16], [17]. There are some minor variations from this trend.…”
Section: Discussionmentioning
confidence: 54%
“…Koskela et al is to research the effect of electricity pricing on the profitability of a PV system and BESS in residential buildings, including detached homes and apartment buildings [4]. Given a set of asset sizes, the optimization of PV system and BESS sizing for a household load is presented in [16]. While the investment of incorporating a BESS was not proven to be profitable for a household load, the work presented by K. Kappner et al [16] did not include an analysis of the profitability considering PV units and a BESS in a large entity capacity.…”
Section: State Of the Artmentioning
confidence: 99%
“…Given a set of asset sizes, the optimization of PV system and BESS sizing for a household load is presented in [16]. While the investment of incorporating a BESS was not proven to be profitable for a household load, the work presented by K. Kappner et al [16] did not include an analysis of the profitability considering PV units and a BESS in a large entity capacity. Z. Iqbal et al explore the potential reduction in electricity costs by implementing a smart home with an energy management system [17].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The topics included in this issue range from wind power to photovoltaic systems [1][2][3] and from biomass to bioliquids and biofuels for heat, electricity, and transport [4][5][6], (1A, 3A). They cover the entire innovation process, ranging from scientific research to innovative approaches for technology implementation and the politics of energy landscapes [5,7] edition comments on the societal debate on the benefits and risks of Germany's "Energiewende" and the conservation aspects of future energy landscapes [8,9].…”
mentioning
confidence: 99%